A Consolidated Effort for Marketing in Commercial Banks - Koirala, Parashar (NRB Economic Review, 2007)
Commercial banks in Nepal still appear to be biased towards the traditional practices for the attraction of potential customers. Meeting the needs of potential customers in the 21st century with the knowledge and training of 20th century is a difficult task. Changes in the marketing strategy within a traditional working structure and system have led the banks towards increasing the non-performing loan (NPL). As every sub-system is a part of a system, a small mistake on the loan disbursement process reflects its implication on the loan recovery process. Hence, a new system in loan disbursement and a loan recovery process makes the bank more effective in its operations. In the new system, all the parties involved in decision-making process should be made responsible to their functions and they need to be penalized accordingly if they fail to promote healthy growth of the banking system.